ANALISIS RASIO LAPORAN ARUS KAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. KARYA MANDIRI SURYA SEJAHTERA MAKASSAR - Syarifuddin Syarifuddin; Iin Kardinah (AkMen JURNAL ILMIAH, 2019)
This study aims to determine the development of net cash flow and find out the financial performance of PT. Mandiri Surya Sejahtera. 2015-2107. This research method is a descriptive data analysis method from the Financial Report of PT Mandiri Surya Sejahtera. Data collection in this study was conducted by interviewing and documenting financial report data. The results of this study indicate that the development of the financial performance conditions of PT Karya Mandiri from 2015-2017 shown by the cash flow analysis tends to decrease. The decrease was caused by a decrease or cash deficit in 2017. Even though the amount of net income obtained in 2017 was greater than that of 2016. However, the amount of cash expenditure in 2017 was greater than cash receipts or in other words the profit gained was largely unrealized into cash, but still in the form of accounts receivable. This condition is because the company cannot manage existing cash flows to be able to generate more cash